A Brief History of ACE - William E. Carnahan (Journal of Applied Communications, 2000)
The American Association of Agricultural College Editors (AAACE) was created on July 10, 1913, when six land grant college agricultural editors met at the University of Illinois. The Illinois gathering was so successful that the founders decided the conference should be an annual affair. The second meeting was a two-day conference, June 25 and 26, 1914, at the University of Kentucky, with seventeen attending. At the Wisconsin meeting in 1915, the AAACE constitution was adopted and the name “American Association of Agricultural College Editors” was established. AAACE was renamed Agricultural Communicators in Education (ACE) in 1978. Since its beginning, ACE has met in 41 states, Washington, DC; and Canada. Some of the more important documents in the archives include: copies of every issue of the newsletter, beginning with Vol. 1, No. 1, November 1919, except three—one each in 1924, 1947 and 1958; copies of every issue of the ACE Quarterly; nearly every annual meeting program since 1914; “The Presidents of ACE,” book; board minutes, directories, regional reports, an AAACE Style Book, and other materials. The materials are a part of the Special Collections of the National Agricultural Library at Beltsville, Maryland. The first AAACE archivist was Clara Bailey Ackerman, in Extension Information in USDA’s (United States Department of Agriculture) Federal Extension Service. She was named archivist at the 1939 AAACE meeting and served through July 1954. The next archivist was Ralph Fulghum, Assistant Director of Extension Information. Other archivists to serve AAACE/ACE include James H. McCormack (1975-1980) and William E. Carnahan (1981- present).